La participation des citoyens aux choix énergétiques généraux - Camilleri, Gérard (Les Cahiers de droit, 1983)
Many citizens have been alarmed by the development of nuclear facilities, especially when the proposed site for a nuclear plant is located in their neibourghood or region. Parliamentary democracy is not particularly appropriate as a means of channeling citizens' apprehensions and commrnyd. Legislative power is delegated every four years or so to elected members of Parliament. Meanwhile, citizens have no say in the business of the State. The administration is even more remote since administrations of government departments, boards and corporations are not elected and parliamentary control is often weak and sometimes non-existent. The frustration of citizens and groups is therefore exacerbated by the lack of access to the decision-making process. Exasperation sometimes leads to violent demonstrations and acts of terrorism. To counter this feeling ofpowerlessness, governments have developed some means of positive participation. Firstly, channels of information have been opened so that rumours can be replaced by facts and objective policy statements. This requires from the Administration that its proposals be fully justified and that preliminary work has been made. Secondly, the development of public inquiries gives interested persons and groups the feeling they are integrated in the decision making process instead of being left outside in the dark. Parliamentary control can be updated to allow for national debates on nuclear policy and its implementation. Finally, the use of the referendum technique at the national, regional or local level would give back to the people their freedom of expression on such issues. The examples set by Austria and Sweden are particularly interesting in this respect. However, the equilibrium between the requirements of democracy and political expediency still remains very hard to find.